Regional Dimensions of Knowledge Processes in the Sectors of Transport and Logistics and ICT in the Zilina Region - Tatiana Corejova; Maria Rostasova; Alena Chrenkova; Emilia Madudova (Communications - Scientific letters of the University of Zilina, 2013)
The paper presents the results of the APVV project - Regional dimensions of knowledge economy, which was solved in the Department of Communications, Faculty of Operation and Economics of Transport and Communications, University of Zilina during 2008 – 2011. The paper briefly describes logistics sector and ICT sector in the Zilina region and their knowledge management. Significant results of the project were achieved through knowledge biography, which maps creation, processing and dissemination of knowledge. Based on this methodology the case studies in selected logistics and ICT enterprises in the Zilina region were created. The results of sectoral analysis and knowledge biographies of enterprises resulted into finding that knowledge is the most strategic “material”; learning is a critical process for maintaining competitiveness of enterprises and that relevant aspects together create key mechanism for regional differentiation.